Critical Factors of the New Islamic Supply Chain Model Through the Lens of Descriptive Data Analysis - Mohd Saifudin, Adam; Othman, Siti Norezam; Mohamed Elias, Ezanee (International Journal of Supply Chain Management, 2017)
This empirical paper is endeavoured to confirm the critical factors of the Islamic supply chain model in Malaysia.  The seven (7) constructs are inclusive of halal integrity, halal logistics practices & industry; halal logistics service providers; halal collaboration (JAKIM & HDC); halal international logistics and confidence on halal certification/log. A quantitative method of descriptive statistics of all the constructs been measured in the survey.  The measurements are being performed by using a perceptual scale.  Each question is answered by using the five-point Likert scale: strongly disagree (1); disagree (2); neither agrees nor disagree (3); agree (4); and strongly agree (5).  A qualitative data in the forms of words from the interview of the halal practitioner is presented. The information in terms of minimum & maximum value, mean and standard deviation of the data are shown.  The result showed all the seven (7) constructs are within the assumption underlying the statistical techniques which addressees’ specific research questions. We describe these constructs for establishing a new model of Islamic halal supply chain and provide a brief introduction of its scope and practices.